3 Feet Under: Is the Traditional Hāngī in Danger of a Cultural Disappearance? - Richardson, Robert (Auckland University of Technology, 2018)
The sharing of familiar foods is but one of the ways a cultural group identifies itself. But what happens if a cultural group begins to lose touch with its food traditions? How does the growing disappearance of these culinary cultural markers affect a cultural groups sense of identity and its spiritual and ancestral connections? In today’s Māori society, the hāngī is one of the last remaining traditional food preparation techniques still in use, but its use in its traditional form is growing more infrequent. Prior to European arrival in New Zealand, the hāngī (earth oven or umu) was used daily as the primary technique for the cooking of kai (Belich, 2007; Leach, 2010). The gradual introduction of European cooking techniques and oven apparatus has relegated the use of the traditional hāngī technique to hui or times of celebration and loss - particularly on the marae (Leach, 2010; Salmond, 1975). Yet even that role is quickly disappearing. Today’s marae kitchens are now equipped like a commercial restaurant or hotel kitchen, while there is now an increasing array of gas fired portable “hāngī” or MultiKai cookers (Coster, 2016; "MultiKai Hāngī Cookers," n.d.; "Te Kohatu Hangi Cookers," n.d.). In this research project, I set out to explore the cultural significance of the hāngī as a cooking technique within Māori society through the voices of those familiar with Te Ao Māori. Food itself continues to play an important part of Māori social gatherings through the concept of manaakitanga, but, in the instance of a hui for example, does it matter in any way if the food is not cooked in the traditional hāngī? Does the non-use of the hāngī as the cooking technique reflect in any way on the prestige of the event and/or on the mana of either guest or host? Through key informant interviews, this research project found two clear, very differing outlooks in how the hāngī is viewed and valued that depended on a person’s personal background. For those that grew up within a strong Māori culture, it is not the hāngī itself that they miss but the times when the events were bigger and more regular. It is these nostalgic recollections around which their affinity with the hāngī is based. For those whose interactions with it began later in life, the hāngī has not only provided a window into Māori culture, but provides both a professional and financial opportunity. But as seen in this study, of arguably greater importance is the role the hāngī plays as a cultural gathering and learning space within Māori culture. It is around the hāngī that many aspects of tikanga, social and environmental protocols, and manaaki are learnt. In doing so, the hāngī provides an anchoring point around which this process of cultural reaffirmation can take place. It is this aspect of the hāngī – the social and cultural educational opportunities that it provides – that this study highlights to be its most valuable today, and is the aspect that Māori are most likely to lose if the hāngī continues to shift to a more commercial practice.
Keywords: Hāngī; NZ food culture; Tikanga; Kai; Māori culture; Marae; Te Ao Māori